Literature Review: Potensi Daun Sirsak (Annona muricata L.) sebagai Obat Penurun Kadar Kolesterol - Nur Aini, Ika; Laily, Rosdiana; Fikky Dian , Roqobih (Fakultas Farmasi Universitas Mahasaraswati Denpasar, 2024)
Cholesterol is a fat or lipid from the sterol group produced by the body. The higher the cholesterol level in the blood, the greater the risk of atherosclerosis, which is the first step in triggering other cardiovascular diseases such as hypertension, coronary heart disease, and even stroke and death. One of the synthetic drugs commonly used to treat high cholesterol is statins, especially atorvastatin. However, long-term use of atorvastatin can cause several side effects, including muscle pain, liver damage, type 2 diabetes, and digestive disorders. Because of the risk of these side effects, many people turn to herbal-based alternative treatments which are considered safer. Self-medication can be done to reduce high cholesterol levels. Self-medication is a community effort to obtain and use traditional medicine independently. One of the traditional medicines that is believed to lower cholesterol levels is soursop leaves. This research aims to look at the potential of soursop leaves as a medicine to lower cholesterol levels and provide a choice for people who want to reduce their cholesterol levels, especially for sufferers of hypercholesterolemia. This article is a literature review article using the literature review study method. A literature search was carried out using the Google Scholar database, namely articles or guidelines on the potential of soursop leaves as a medicine to lower cholesterol levels published in the last 10 years. The research results show that soursop leaves have a significant effect on reducing cholesterol levels. So soursop leaves can be considered a safe and effective herbal treatment for hypercholesterolemia.